Perianal Abscess Caused by Urethral Foreign Body: A Case Report - Sayaka Hoshino; Kenji Obara; Kazutoshi Yamana; Fumio Ishizaki; Masaki Murata; Tatsuhiko Hoshii; Yoshihiko Tomita (IJU Case Reports)
ABSTRACT Introduction We report a case of perianal abscess that developed after the presence of a urethral foreign body for 15 months. Case Presentation A 14‐year‐old boy with intellectual disability due to agenesis of the corpus callosum presented to our hospital with complaints of perianal erythema, swelling, and pain. The patient admitted to self‐inserting an allene fiber broom ear 15 months ago. A few days after the insertion, he was treated with antibiotics for hematuria and micturition pain. The symptoms resolved spontaneously 2 months later, although the foreign body was not removed. Computed tomography and magnetic resonance imaging demonstrated a perineal linear structure running anterior to posterior. The urethral foreign body was removed by cystourethroscopy and grasper. Conclusion Medical professionals should be aware of the possibility of underlying cognitive and behavioral problems and should be vigilant in screening and treating individuals with refractory lower urinary tract inflammation or hematuria.